2014
DOI: 10.1007/s00775-014-1229-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Fe(III) binding sites of human serum transferrin with EPR at 275 GHz

Abstract: We report 275 GHz EPR spectra of human serum transferrin. At this high microwave frequency the zero-field splitting between the magnetic sublevels of the high-spin [Formula: see text] sites can be accurately determined. We find the zero-field splitting to be a sensitive probe of the structure of the transferrin iron-binding sites. Signals arising from iron bound to the transferrin N-lobe can clearly be distinguished from signals from iron bound to the C-lobe. Moreover, our spectra show that the structure of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 77 publications
(104 reference statements)
0
10
0
Order By: Relevance
“…Before closing, we should note that experimental measurements of iron-bound hTF, including Mössbauer (34,35) and electron paramagnetic resonance (EPR) spectroscopy (34,36,37), produces results that indicate a high-spin Fe(III) sextet: S eff = 5/2. From our perspective, the main contribut- ing factor of the difference between our S eff values and these experiments stem from the experimental requirement of low temperatures and high external magnetic fields; as an example, the EPR experiment of (37) was performed under external fields spanning 7.5 to 12T, up to a temperature of 90K.…”
Section: Resultsmentioning
confidence: 99%
“…Before closing, we should note that experimental measurements of iron-bound hTF, including Mössbauer (34,35) and electron paramagnetic resonance (EPR) spectroscopy (34,36,37), produces results that indicate a high-spin Fe(III) sextet: S eff = 5/2. From our perspective, the main contribut- ing factor of the difference between our S eff values and these experiments stem from the experimental requirement of low temperatures and high external magnetic fields; as an example, the EPR experiment of (37) was performed under external fields spanning 7.5 to 12T, up to a temperature of 90K.…”
Section: Resultsmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectra also support slightly (but not drastically) different properties between the N- and C-sites. Recently, EPR studies of iron transferrin at high frequency microwaves (275 GHz) [ 34 , 35 ] have been reported. For analysis, the fourth-order term, (q = −4, ⋯, 4), is added to the usual spin Hamiltonian Equation [ 36 ]: where is the g-tensor; B is the magnetic field; S is the effective spin operator; and , , and are the x , y , and z elements, respectively.…”
Section: Redox-active Iron In Bloodmentioning
confidence: 99%
“…Electron paramagnetic resonance (EPR) spectra also support slightly (but not drastically) different properties between the N-and C-sites. Recently, EPR studies of iron transferrin at high frequency microwaves (275 GHz) [34,35] have been reported. For analysis, the fourth-order term, ∑ B q 4 O q 4 (q = −4, .…”
Section: N-lobe C-lobe Fe2 Fe1mentioning
confidence: 99%
“…7-20 A number of experimental studies have been carried out to understand the geometric and electronic structure and the ion release pathway of sTf. 4,5,7,21,22 As the magnetic anisotropy is very small (<0.5 cm −1 ) due to half-filled d 5 iron, [23][24][25][26][27] the isomer shift and quadrupolar splitting of Fe derived from Mössbauer spectroscopy (MB) are often used to elucidate the electronic structure of the active site. [28][29][30] As far as ion transmission pathways are concerned, several molecular dynamics simulations are carried out by varying the protonation state of the nearby amino acids such as salt bridged Lys, Tyr188, and carbonate.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34] A plethora of spin Hamiltonian parameters (SH) derived from MB spectroscopy and EPR spectroscopy are available which can directly reveal the electronic structure of iron sTf in physiological pH. 15,[23][24][25][26]28,29,[35][36][37][38] Computing these SH parameters can directly reveal the coordination environment of Fe(III) in sTf which was never attempted before.…”
Section: Introductionmentioning
confidence: 99%